(untitled) (Research, Society and Development, 2021)
The biochar of the Pequi peel represents a sustainable alternative in the process of treating effluents through adsorption system. This study investigates the adsorption capacity in a fixed bed column of the activated biochar from pequi peel (ABPP) to remove the components. The biochar was obtained by pyrolysis, which was activated with zinc Chloride - ZnCl₂. Through the Thomas model, it was found that the concentration of Paracetamol of 5 mg L-1 obtained 3.21 mg g-1 of drug adsorption, which was higher than the adsorption obtained with the concentrations of 10 mg L-1 (3.02 mg g-1) and 20 mg L1 (1.22 mg g-1). Methylene blue was tested with a concentration of 3 mg L-1, adsorbing 8.07 mg g-1. The data fit the Thomas model with an R² higher than 0.90. The capacity of ABPP to adsorb methylene blue and Paracetamol was satisfactory, with adsorbing significant.